2013
DOI: 10.1007/s00432-013-1499-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of E-cadherin, Twist, and p53 and their prognostic value in patients with oral squamous cell carcinoma

Abstract: E-cadherin is an independent marker for survival prediction in OSCC. Co-evaluation of E-cadherin and p53 expression might be a valuable tool for predicting OSCC patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 43 publications
6
68
2
4
Order By: Relevance
“…40 E-cadherin is a hallmark in this process, being involved in the epithelial-to-mesenchymal transition mechanism also in SCC, whereas a downregulation of this cell adhesion molecule is associated with a poor prognosis in terms of recurrence and mortality. 12,18,40 Contrarily, recent reports showed that p63 expression reintroduces epithelial characteristics in mesenchymal type cells and therefore reverses the mesenchymal tendency of epithelial tumors. 18,31 These 2 markers seem to act as regulatory molecules in the epithelial-to-mesenchymal transition equilibrium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…40 E-cadherin is a hallmark in this process, being involved in the epithelial-to-mesenchymal transition mechanism also in SCC, whereas a downregulation of this cell adhesion molecule is associated with a poor prognosis in terms of recurrence and mortality. 12,18,40 Contrarily, recent reports showed that p63 expression reintroduces epithelial characteristics in mesenchymal type cells and therefore reverses the mesenchymal tendency of epithelial tumors. 18,31 These 2 markers seem to act as regulatory molecules in the epithelial-to-mesenchymal transition equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggest that a change in the expression of these 2 molecules could be a common event in oral SCC in dogs, similar to what occurs in humans. 7,12 Epithelial-to-mesenchymal transition is an essential process in tumor progression, being implicated in gain of invasiveness and capacity to escape from the primary site and metastasize. 40 E-cadherin is a hallmark in this process, being involved in the epithelial-to-mesenchymal transition mechanism also in SCC, whereas a downregulation of this cell adhesion molecule is associated with a poor prognosis in terms of recurrence and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 It has been reported that the loss of protein expression of CDH1 is also associated with an increased invasive potential in head and neck cancer. 42 In a study conducted on clinical samples collected from patients with tongue squamous cell carcinoma, a significantly lower CDH1 mRNA expression level than in the corresponding noncancerous tissues was shown. 31 In our study, no significant differences were found between the CDH1 gene expression levels of the tumors and the surgical margin samples.…”
Section: Cdh1mentioning
confidence: 99%